The tomato cis–prenyltransferase gene family. (31st December 2012) - Akhtar, Tariq A.; Matsuba, Yuki; Schauvinhold, Ines; Yu, Geng; Lees, Hazel A.; Klein, Samuel E.; Pichersky, Eran
Summary: cis– prenyltransferases (CPTs) are predicted to be involved in the synthesis of long‐chain polyisoprenoids, all with five or more isoprene (C5) units. Recently, we identified a short‐chain CPT, neryl diphosphate synthase (NDPS1), in tomato ( Solanum lycopersicum ). Here, we searched the tomato genome and identified and characterized its entire CPT gene family, which comprises seven members ( SlCPT1–7, with NDPS1 designated as SlCPT1 ). Six of the SlCPT genes encode proteins with N–terminal targeting sequences, which, when fused to GFP, mediated GFP transport to the plastids of Arabidopsis protoplasts. The SlCPT3–GFP fusion protein was localized to the cytosol. Enzymatic characterization of recombinant SlCPT proteins demonstrated that SlCPT6 produces Z, Z– FPP, and SlCPT2 catalyzes the formation of nerylneryl diphosphate while SlCPT4, SlCPT5 and SlCPT7 synthesize longer‐chain products (C25–C55). Although no in vitro activity was demonstrated for SlCPT3, its expression in the Saccharomyces cerevisiae dolichol biosynthesis mutant ( rer2 ) complemented the temperature‐sensitive growth defect. Transcripts of SlCPT2, SlCPT4, SlCPT5 and SlCPT7 are present at low levels in multiple tissues, SlCPT6 is exclusively expressed in red fruit and roots, and SlCPT1, SlCPT3 and SlCPT7 are highly expressed in trichomes. RNAi‐mediated suppression of NDPS1 led to a large decrease in β–phellandrene (which is produced from neryl diphosphate), with greater reductions achieved with the general 35S promoter compared to the trichome‐specific MKS1 promoter. Phylogenetic analysis revealed CPT gene families in both eudicots and monocots, and showed that all the short‐chain CPT genes from tomato ( SlCPT1, SlCPT2 and SlCPT6 ) are closely linked to terpene synthase gene clusters.